Effect of Nonsteroidal Anti-inflammatory Drug (NSAID) in Disease Relapse, Progression, and Development of Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis: NSAID and IBD - Darmadi; Imelda Rey (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2022)
This systematic review and meta-analysis investigated the association between nonsteroidal anti-inflammatory drugs (NSAIDs) and inflammatory bowel disease (IBD). Pooled analysis showed no significant association in disease relapse (OR 0.97; 95% CI 0.70–1.35; p = 0.86) and disease worsening (OR 2.06; 95% CI 0.92–4.57; p = 0.08) of existing IBD in patients receiving NSAID. In patients without prior IBD diagnosis, NSAID medication was significantly associated with risk of new-onset IBD (OR 1.51; 95% CI 1.19–1.92; p = 0.0008). Given the varied effects of NSAIDs on IBD, careful management and consideration of dosage and frequency are essential in IBD patients. Despite these insights, the heterogeneity of study designs and small sample sizes in some cases call for further large-scale research to validate these findings.